ANALISIS KADAR TIMBAL (Pb) PADA PEKERJA PENGELASAN DI DAERAH SAMARINDA SEBERANG DENGAN METODE SPEKTROFOTOMETER SERAPAN ATOM (SSA) - Wijaya, Fransiska Angeli Wijaya Angeli (Jurnal Sains dan Teknologi Laboratorium Medik, 2024)
Welding is a process of permanently joining metals by heating the metal to the melting point. This process will cause the accumulation of heavy metals in the air. UV and IR radiation is a kind of environmental exposure that can occur during welding. Long-term exposure to welding rays can cause problems with the lens of the eye including loss of transparency, discomfort in activities, itching in the eye area and breathing. Lead that is inhaled and enters the lungs will be associated with blood. Lead that is absorbed by the body will bind to red blood cells and then be distributed into the blood, extracellular fluid, and some soft places (liver, kidneys, and nerves) and mineral tissues (bones and teeth). The purpose of this study was to determine the blood lead levels of welding workers based on length of work, age, and working period with a normal limit value of